Holothurian fucosylated chondroitin sulfates and their potential benefits for human health: Structures and biological activities. (1st January 2022) - Xu, Hui; Zhou, Qian; Liu, Bin; Chen, Feng; Wang, Mingfu
Abstract: Fucosylated chondroitin sulfates (FCS) are a sulfated polysaccharide exclusively existing in the body wall of sea cucumber. FCS possesses a mammalian chondroitin sulfate like backbone, namely repeating disaccharides units composed of GlcA and GalNAc, with fucosyl branches linked to GlcA and/or GalNAc residues. It is found that FCS can prevent unhealthy dietary pattern-induced metabolic syndromes, including insulin resistance and β-cell function improvement, anti-inflammation, anti-hyperlipidemia, and anti-adipogenesis. Further studies show that those activities of FCS might be achieved through positively modulating gut microbiota composition. Besides, FCS also show therapeutic efficacy in cancer, HIV infection, and side effects of cyclophosphamide. Furthermore, bioactivities of FCS are closely affected by their molecular weights, sulfation pattern of the fucosyl branches, and chain conformations. This review summarizes the recent 20 years studies to provide references for the future studies and applications of FCS in functional foods or drugs. Graphical abstract: Unlabelled Image Highlights: Systematically reviewing the structural characteristics of FCSs that have been reported at present Discussing the bioactivities of FCS to indicate their applications in functional food or drug Indicating the structure-activity relationships of FCS